Multi-response optimization of the adsorption properties of activated carbon produced from H2SO4 activated sludge: Effects of washing with HCl - Ben Ali, Majda; Benzaouak, Abdellah; Tangarfa, Mariam; Abrouki, Younes; Belekbir, Soukayna; hazzat, Mouatamid EL; El Hamidi, Adnane; Abdelouahed, Lokmane (Case studies in chemical and environmental engineering, 2025)
This study explores the valorization of sludge for producing activated carbon, recognized for its efficiency in removing textile dyes. Various analytical techniques were used to characterize sludge, biochar, H2SO4-activated carbon (HS), and H2SO4-activated carbon washed with HCl (HSC). The HSC sample exhibited increased porosity, with a significant enhancement in specific surface area from 3.4 m2/g to 268.8 m2/g, along with increased pore volume. Adsorption kinetics followed a pseudo-first-order model for HS (Qe,exp = 82 mg/g) and a pseudo-second-order model for HSC (Qe,exp = 98.89 mg/g). These findings provide valuable insights into the potential application of these adsorbents for methylene blue removal.